2015
DOI: 10.1177/1359105314566613
|View full text |Cite
|
Sign up to set email alerts
|

A breath of fresh air: Images of respiratory illness in novels, poems, films, music, and paintings

Abstract: The nature and severity of respiratory disease are typically expressed with biomedical measures such as pulmonary function, X-rays, blood tests, and other physiological characteristics. The impact of respiratory illness on the sufferer, however, is reflected in the stories patients tell: to themselves, their social environment, and their health care providers. Behavioral research often applies standardized questionnaires to assess this subjective impact. Additional approaches to sampling patients' experience o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…All are active in the area and publish in the field of ‘literature and medicine’ and ‘medical humanities’ (e.g. Kaptein et al, 2015 ; Murray, 2000 ; Murray and Gray, 2008 ; Sesker et al, 2016 ; Smyth et al, 1999 ).…”
Section: Methodsmentioning
confidence: 99%
“…All are active in the area and publish in the field of ‘literature and medicine’ and ‘medical humanities’ (e.g. Kaptein et al, 2015 ; Murray, 2000 ; Murray and Gray, 2008 ; Sesker et al, 2016 ; Smyth et al, 1999 ).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, searches on lung cancer+movies or cardiovascular disease+movies returned few relevant hits. 10 The searches were independently re-performed by the second author (AGK) (on 24 April 2016). No studies specifically reported on the effects of smoking-related disease education or awareness in mainstream TV series or movies on tobacco control.…”
mentioning
confidence: 99%
“…34,35 Similarly, the arts can be used to illuminate the experience of the person who is ill (sometimes literally giving a non-verbal client a language through which to express themselves) and support clinicians in expressing or reflecting on their own experiences. The broad range of films and novels on health themes attests to the power of the arts as a means of reflection on what it is to be human and to be ill. 36,37 The processes for ensuring congruence between arts and health and clinical care and environments is as yet relatively unformed but ideally should seek to better understand the arts, culture and leisure engagement of patients: helpful guidance on curatorship in arts and health is emerging. 32,38 Examples of such work through engagement of doctors, nurses and patients with an arts director and range of artists in Tallaght University Hospital in Dublin include a triptych of new compositions by composer Ian Wilson, reflecting on the major illnesses of older age; a mental health film festival where each film was followed by discussion facilitated by a psychiatrist and a film maker; a mural project in the paediatric unit and a hospital workplace choir for staff.…”
Section: Arts and Healthmentioning
confidence: 99%